Performance analysis of conditional integrator in NPID controller as cutting force compensator for machine tools application - Saidin, I. A. (Springer Science and Business Media Deutschland GmbH, 2022)
In machine tools application, a control mechanism is needed to compensate the presence of disturbance force. Disturbance force can be in many forms depends on the machine tool used or the application. There are a few adaptations that can be made to a controller to achieve a robust control mechanism. The aim of this research is to evaluate the effect of adapting a conditional integrator in a Nonlinear Proportional-Integral-Derivative (NPID) controller to compensate cutting force disturbance in XY ball screw drive table. The control mechanism is evaluated based on the Fast Fourier Transform (FFT) error generated by when simulating the machine operation. The comparison between the normal NPID and NPID with conditional integrator are made in terms of fundamental peak frequency of FFT error to conclude the effect of conditional integrator for cutting force compensation. The outcomes concluded that the addition of conditional integrator further improves the control mechanism as a disturbance compensator.